The Use Of The Direct Method In The Classroom To Improve Pronunciation - Tovar Castillo, Jenny Del Carmen (2012)
1. The origins of the Direct Method 2. Berlitz Schools and their approach to English teaching 3. Ideas on how to teach pronunciation through the Direct Method